Fifth international Symposium on the lacertids of the Mediterranean Basin Lipari, Aeolian Islands, Sicily, Italy, 7-11 May 2004 - Lo Cascio, Pietro; Corti, Claudia (Atti, 2004)
The volume collects the contributions to the Fifth International Symposium on the Lacertids of the Mediterranean Basinheld on the island of Lipari between 7 and 11 May 2004. The study of the Mediterranean lacertid lizards represents a key point for understanding the mechanisms regulating the evolution of the Mediterranean's ecosystems and in particular those ones related to islands. Conservation of biodiversity is the main target that such a knowledge significantly contributes to fulfil.